Everyone who is gone is here : the United States, Central America, and the making of a crisis - Blitzer, Jonathan (Penguin Press, 2024)
"Everyone who makes the journey faces an impossible choice. Hundreds of thousands of people who arrive every year at the US-Mexico border travel far from their homes. An overwhelming share of them come from El Salvador, Guatemala, and Honduras, although many migrants come from farther away. Some are fleeing persecution, others crime or hunger. Very often it will not be their first attempt to cross. They may have already been deported from the United States, but it remains their only hope for safety and prosperity. Their homes have become uninhabitable. They will take their chances. This vast and unremitting crisis did not spring up overnight. Indeed, as Blitzer dramatizes with forensic, unprecedented reporting, it is the result of decades of misguided policy and sweeping corruption. Brilliantly weaving the stories of Central Americans whose lives have been devastated by chronic political conflict and violence with those of American activists, government officials, and the politicians responsible for the country's tragically tangled immigration policy, Blitzer reveals the full, layered picture for the first time."-- Book jacket.